2000
DOI: 10.1046/j.1440-1754.2000.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine for the management of autonomic dysfunction after severe traumatic brain injury

Abstract: This case report describes a child with severe traumatic brain injury with clinical features of autonomic dysfunction in the immediate post-traumatic period. A history of severe asthma in this child contraindicated the use of beta-blockers, the first line approach, and she was managed with bromocriptine (0.05 mg/kg t.d.s) with good effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…These dystonic movements, if not managed in a timely manner, can result in generalised motor rigidity and pose difficulties during supportive nursing care in the ICU. A search of the literature showed that various drugs such as morphine, (1,6) a or b blockers, (3,9,10) dopamine agonists (6,7,13) and benzodiazepines (3,14) could be used to alter central nervous system responsiveness by virtue of changes to a, b, GABA, dopamine or opiate receptors, respectively. As the dystonic movements subsided in our patient when intermittent boluses of IV midazolam were given, continuous IV infusion of midazolam along with morphine was administered to control the abnormal movements, with good results.…”
Section: Discussionmentioning
confidence: 99%
“…These dystonic movements, if not managed in a timely manner, can result in generalised motor rigidity and pose difficulties during supportive nursing care in the ICU. A search of the literature showed that various drugs such as morphine, (1,6) a or b blockers, (3,9,10) dopamine agonists (6,7,13) and benzodiazepines (3,14) could be used to alter central nervous system responsiveness by virtue of changes to a, b, GABA, dopamine or opiate receptors, respectively. As the dystonic movements subsided in our patient when intermittent boluses of IV midazolam were given, continuous IV infusion of midazolam along with morphine was administered to control the abnormal movements, with good results.…”
Section: Discussionmentioning
confidence: 99%
“…It acts on the corpus striatum and the hypothalamus [29]. It may help in PSH, due to its action on dopaminergic transmission [30] [31]. Unfortunately, there is no a lot of studies on the efficacy of bromocriptine in traumatic brain injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that neuroleptic malignant syndrome is caused by dopamine blockade, but the role of dopamine in the pathophysiology of PSH remains unclear. Bromocriptine is reported to be effective for PSH, and the efficacy is enhanced if used in combination with other medicines, especially morphine [27,38]. The effect of bromocriptine is modest and delayed.…”
Section: Dopamine Agonists and Antagonistsmentioning
confidence: 99%